KONTRIBUSI KINERJA TUTOR BELAJAR TERHADAP PERFORMA AKADEMIK PESERTA DIDIK PROGRAM PAKET C REMIDI - Mohammad Efendi (Jurnal Ilmiah Visi, 2007)
This research was aimed at analyzing instructor’s performance towards the academic performance of the students from Package C Remedial Program in the District and the Municipality of Malang. Based on the collected data through questioners, documentations, self-inventory sheets as well as instructor’s performance observation sheets, it can be concluded that the performance of instructors has significantly correlated towards academic performance of the students from Package C remedial Program in the District and Municipality of Malang. It is suggested if this model would be followed up as an alternative short cut for those who have failed High School National Exams, then we need to accurately prepare the readiness of Package C personnel, time, cost, and its setting up system.